PENDAMPINGAN IMPLEMENTASI PENYUSUNAN HPP DAN LAPORAN KEUANGAN BERBASIS EXCEL PADA CV SBI - Lutvie Novita Zalwa; Khoirunnisa Khoirunnisa; Milasiti Nursadiyah; Siti Lena Al Barokah; Sekar Ayu Kusuma Dewi; Felix Karya Surya; Mimin Widaningsih (Universitas Mataram, 2026)
CV Sagara Biantara Indonesia is a micro, small, and medium enterprise (MSME) operating in the freight forwarding and trucking services sector that still relies on a manual financial recording system, reflecting limited understanding of systematic and automated financial reporting. This condition results in inefficient financial management, a high risk of recording errors, and an inability to produce accurate and relevant financial information. This community service activity aims to assist in the design and implementation of a Cost of Production calculation system and Microsoft Excel-based financial reports to enhance the company's capability in independently preparing income statements and balance sheets. The method employed is a participatory and applicative approach, carried out through the stages of needs identification, system design, implementation, technical assistance, evaluation, and sustainability monitoring. The results indicate that the mentoring successfully produced a Cost of Production calculation template and Microsoft Excel-based financial report formats tailored to the company's needs, capable of improving transaction recording regularity, accelerating cost calculation processes, and reducing the risk of manual recording errors. Furthermore, the partner gained an improved understanding of independent financial report preparation. Therefore, the implemented system contributes to enhanced financial management effectiveness, supports more accurate and sustainable managerial decision-making, and delivers tangible impact for CV SBI in determining profit per transaction more precisely and fostering sustainable business development.